Pelo e-processo justo : construção de um modelo mínimo para a virtualização do processo judicial - Gillet, Sérgio Augusto da Costa (2017)
This dissertation aims to the analysis of the virtualization of process, observing the scientific movements, the principiological (re)construction, and the constitutional accommodation that derives. For that, it investigates the movements of constitutionalization of the civil process and its virtualization by the use of informational and communicational technologies to demonstrate in what way they converge and are influenced by the contemporary Net Society, especially when is observed inserted in a Democratic Rule of Law. It utilizes the hypothetic-deductive method of approaching, in which it conjectures the scientific-juridical autonomy of the e-process, analysing the construction of a specific principiologic body and its conjugation with the procedural fundamental rights. It concludes that the e-process constitutes a singular institute inserted in the process theory and compound of a specific normative body of rules and principles of its own. From this derives that these attributes must be observed by the Judiciary Power at the implementation of the e-process as a (new) minimum model, suggesting the designation as fair e-process for it aligns with the notion of the fundamental right to a fair trial whereas minimum model of procedural conformation to be offered, guaranteed and observe by State to free up an adequate and effective tool for tutelage of rights and the social pacification.